Rethinking the nature of fascism : comparative perspectives - Pinto, António Costa 1953- Hrsg (Palgrave Macmillan, 2011)
Introduction : Fascism and other '-isms' / António Costa Pinto -- Decomposition and recomposition of theories : how to arrive at useful ideas explaining Fascism / Stein U. Larsen -- Desperately seeking 'generic Fascism' : some discordant thoughts on the academic recycling of indigenous categories / Michel Dobry -- Fascism and culture : a mosse-centric and meta-narrative (or how Fascist studies reinvented the wheel) / Roger Griffin -- Theories of Fascism : a critique from the perspective of women's and gender history / Kevin Passmore -- Fascism and religion / John Pollard -- Ideology, propaganda, violence and the rise of Fascism / Roger Eatwell -- Political violence and institutional crisis in interwar southern Europe / Giulia Albanese -- Ruling elites, political institutions and decision-making in Fascist-era dictatorships : comparative perspectives / António Costa Pinto -- Fascism, 'licence' and genocide : from the chimera of rebirth to the authorization of mass murder / Aristotle Kallis -- Concluding remarks / Adrian Lyttelton